Anticipated Pain and Pain Experience Among Orthodontic Patients: Is there any Difference? - Kafle, Dashrath; Rajbhandari, A (Kathmandu University Medical Journal, 2013)
Background Orthodontic treatment is taken as a painful procedure by most of the patients. The pain can be experienced during different procedures like separator placement, banding, bonding, extraction as well as arch wire activation and debonding. There are very few studies done on the anticipated pain and pain experienced among mentioned orthodontic procedures. Objectives To compare the anticipated pain and pain experience among the patients going for comprehensive orthodontic treatment. Methods Total 45 patients going for comprehensive orthodontic therapy are enrolled into the study. They are given a 100mm Visual Analogue Scale (VAS) for pain. The anticipated pain as well as perceived pain after different orthodontic procedures are recorded on the VAS by patients and returned back to orthodontic office. The data are analyzed by SPSS 16.00 software by paired and independent t-test for the statistical significance. Results The result showed that there is significant difference between the anticipated pain before orthodontic treatment and the pain experienced following orthodontic treatment. It also showed that perception of pain between two sexes is significantly different. The comparison of anticipated pain among male and female does not show any significant difference, however the pain felt after separator placement as well as after orthodontic bonding is significantly different in two sexes. Conclusion The level of anticipated pain before orthodontic treatment is higher than the real pain experienced after orthodontic procedures. So it is better to counsel and explain the patients about the orthodontic treatment and procedures. Kathmandu University Medical Journal | Vol.10 | No. 2 | Issue 38 | Apr – June 2012 | Page 71-73 DOI: http://dx.doi.org/10.3126/kumj.v10i2.7348